Comparison of different surgical techniques in distal pancreatectomy: an experimental study in a porcine model - Gehrig, Tobias; Fonouni, Hamidreza; Müller, Beat P.; Golriz, Mohammad; Abbasi Dezfouli, Sepehr; Nickel, Felix; Esmaeilzadeh, Majid; Brand, Karsten; Tahmasbi Rad, Morva; Hughes, Katherine M.; Hinz, Ulf; Büchler, Markus W.; et al. (Surgical innovation, 2011)
Aims. Different surgical transection methods have been used for distal pancreatectomy (DP), but none of them has yet achieved perfect results. This study compares 2 standard transection techniques with the alternative LigaSure technique. Methods. Forty-eight pigs underwent a DP. Sixteen animals were operated on with a scalpel followed by hand suturing. Sixteen pigs received a DP using an Endo GIA, and the pancreas of 16 pigs was transected with LigaSure. The transection surface of remnant pancreas was observed for liquid collection and abscess on postoperative day 7. Results. Operating time on the day of DP was significantly different, with a shorter operating time in the stapler and LigaSure groups. The morbidity on postoperative day 7 was similar in all groups. Conclusion. In the present experimental animal study, LigaSure seems to be fast and safe as well as comparable with the standard transection and closure techniques in DP.
Gesehen am 02.10.2023
Richtiger Name vom 5. Autor: Sepehr Abbasi